Kérdőjel - A Szegedi Televíziós Ifjúsági Érdekvédelem Egyesület műsora
115th issue, 100th anniversary of "Bakter" boarding school, colour of skin, loneliness, festival day of Újszeged, badminton competition, sports, quiz on traffic rules